DEVELOPMENT OF AN ELECTRONIC MODULE BASED ON PBL-STEM IN A CONTEXTUAL ETHNOSCIENCE LEARNING “RED BRICK MAKING” TO IMPROVE STUDENTS’ PROBLEM-SOLVING SKILLS - Devhia Riska Noviati; Asri Widowati (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2025)
This research aims to: (1) produce an electronic science modules based on PBL-STEM in ethnoscience learning “red brick making” that are feasible to improve problem solving skills; (2) determine the practicality of electronic science modules based on PBL-STEM in ethnoscience learning “red brick making” “ has been produced in improving problem solving skills; (3) determine the effectiveness of electronic science modules based on PBL-STEM in ethnoscience learning “red brick making” has been produced in improving problem solving skills. This research is development research by adapting Thiagarajan’s 4-D model consisting of Define, Develop, Design, and Disseminate. This research involved 2 expert lecturers as validators, as well as 30 seventh-grade students of SMP N 3 Banguntapan as research subjects. The data analysis technique used qualitative and quantitative analysis. The effectiveness of LKPD through prerequisite test, paired sample t-test, and effect size test. The results showed that: (1) there has been produced electronic modules based on PBL-STEM on ethnoscience learning “red brick making” is very feasible to use in science learning; (2) electronic modules based on PBL-STEM on ethnoscience learning “red brick making” has been produced is very practical in improving students’ problem solving skills (3) electronic modules based on PBL-STEM on ethnoscience learning “red brick making” has been produce is very effective in improving students’ problem solving skills.